2023
DOI: 10.1098/rstb.2022.0120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous elevation of corticosterone on immunity and the skin microbiome of eastern newts ( Notophthalmus viridescens )

Abstract: The amphibian chytrid fungus, Batrachochytrium salamandrivorans ( Bsal ) threatens salamander biodiversity. The factors underlying Bsal susceptibility may include glucocorticoid hormones (GCs). The effects of GCs on immunity and disease susceptibility are well studied in mammals, but less is known in other groups, including salamanders. We used Notophthalmus viridescens (eastern newts) to test the hypothesis that GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 102 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…This may suggest that a host response like glucocorticoid release may play a role. In eastern newts (Notophthalmus viridescens), corticosterone was not considered to be a major factor in immunity (Pereira et al, 2023), but in salamanders (Plethodon shermani) differences were seen between corticosterone and chytridiomycosis resistance (Fonner et al, 2017), suggesting that this relationship may need to be further evaluation, specifically in frogs. Additionally, longitudinal sampling of the same individuals throughout the transportation process would allow for better temporal resolution, identifying shifts in composition and taxa, and improved statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that a host response like glucocorticoid release may play a role. In eastern newts (Notophthalmus viridescens), corticosterone was not considered to be a major factor in immunity (Pereira et al, 2023), but in salamanders (Plethodon shermani) differences were seen between corticosterone and chytridiomycosis resistance (Fonner et al, 2017), suggesting that this relationship may need to be further evaluation, specifically in frogs. Additionally, longitudinal sampling of the same individuals throughout the transportation process would allow for better temporal resolution, identifying shifts in composition and taxa, and improved statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found decreased plasma bacterial killing ability and melanomacrophage centre and lower skin microbiome after long-term treatment (26 days), compared with short-term treatment (5 days), but these changes were not associated with corticosterone treatment. These results demonstrate plasma corticosterone increases may not result in immune changes in the eastern newt, at least in the investigated immune aspects [ 53 ].…”
Section: Stress-related Immunomodulationmentioning
confidence: 99%
“…It is worth mentioning that in amphibians, the resident skin microbiota plays an antimicrobial role, helping to eliminate pathogens such as the Bd fungus and the ranavirus [47][48][49][50][51]. This theme issue adds to evidence that the microbiome composition is an essential component of the immune system in tadpoles and adult anurans (X. laevis and Pseudacris regilla) and salamanders (Notophthalmus viridescens) [52][53][54]. Specifically, [52] demonstrates that experimental reductions of the microbiome, by using antimicrobial treatments, during embryonic and larval stages reduced microbial richness and diversity and altered community composition in tadpoles (X. laevis) prior to metamorphosis, which could lead to increased disease susceptibility in amphibian tadpoles and adults.…”
Section: Amphibian Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several parts of the feedback cascade appeared to be functional (see below). Despite the well-established influence of the gut microbiota on immune system modulation and its impact on the CNS, these tripartite connections remain elusive in wild populations (Hird, 2017;Davidson et al, 2020;Madden et al, 2022;Pereira et al, 2023), particularly during the early stages of development, in contrast to the studies in humans and mice (Martin et al, 2018;Francella et al, 2022;Lynch et al, 2024).…”
Section: Gut Microbial Diversity Not Associated With Immunity and Stressmentioning
confidence: 99%